Peran Serta Masyarakat Dusun Vatutela Kelurahan Tondo Kota Palu Terhadap Pelestarian Kawasan Hutan Lindung (Suatu Kajian Dari Aspek Hukum Kehutanan) - sari, Dewi kemala; Uddin, Abdul Karim; Hafid, Abdul Rahman (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Communities in and around the forest have the right to obtain a life that the forest produces, in addition to this right the community can also utilize the forest and forest products in accordance with applicable laws and regulations, such as knowing forest allotment plans, forestry information, providing information, suggestions, considerations in forestry development, and supervise the implementation of forestry development either directly or indirectly. This research is empirical research, namely research obtained from experience, and information obtained from direct interviews with various sources and related agencies. The role of the community is carried out to increase awareness in protecting and managing the environment, increasing independence, community empowerment, and partnerships, developing community capabilities and pioneering, developing community responsiveness to carry out social supervision; and develop and maintain local culture and wisdom in the context of preserving environmental functions.